Effect of Three Types of Planting Media and Nutrition on the Growth and Yield of Lettuce (Lactuca sativa L.) - Wandana, Alit; Amalia, Lia; Taryana, Yana (Institute of Computer Science (IOCS), 2021)
The experiment was conducted for three months, from August to October 2019. At the horticultural greenhouse of the Center for Supervision and Certification of Food and Horticultural Plant Seeds (BPSBTPH) in the province of West Java. The purpose of the experiment is research to study the interaction effect of three types of growing media and nutrients on growth and yield of lettuce plants. This research is descriptive and verified by an experimental approach in the horticultural greenhouse of the Center for Supervision and Certification of Food and Horticultural Plant Seeds (BPSBTPH) in the province of West Java. The experimental design used is the